2015
DOI: 10.1039/c5nj01306b
|View full text |Cite
|
Sign up to set email alerts
|

An easy synthetic access to new pyrazole spiro derivatives from 3-amino-1-phenyl-2-pyrazolin-5-one

Abstract: Pyrazole and pyrazolone moieties have shown important biological activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…In 2015, the Khouili/Faustino group found that commercially available 5-amino-2-phenyl-2,4-dihydro-3H-pyrazol-3-one 90 can react with benzaldehyde 91 to provide access to the unexpected spiro derivative 92 containing two pyrazolone units under Knoevenagel conditions, in refluxing ethanol with the presence of a base (pyridine or triethylamine) (Scheme 38a). [48] Pyridine base had 45 % yield, whereas triethylamine had 35 %. Furthermore, an extra molecule of R D 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 benzaldehyde could continue the reaction, further obtaining a more complicated polycyclic system 93.…”
Section: Othersmentioning
confidence: 98%
See 1 more Smart Citation
“…In 2015, the Khouili/Faustino group found that commercially available 5-amino-2-phenyl-2,4-dihydro-3H-pyrazol-3-one 90 can react with benzaldehyde 91 to provide access to the unexpected spiro derivative 92 containing two pyrazolone units under Knoevenagel conditions, in refluxing ethanol with the presence of a base (pyridine or triethylamine) (Scheme 38a). [48] Pyridine base had 45 % yield, whereas triethylamine had 35 %. Furthermore, an extra molecule of R D 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 benzaldehyde could continue the reaction, further obtaining a more complicated polycyclic system 93.…”
Section: Othersmentioning
confidence: 98%
“…In 2015, the Khouili/Faustino group found that commercially available 5‐amino‐2‐phenyl‐2,4‐dihydro‐3 H ‐pyrazol‐3‐one 90 can react with benzaldehyde 91 to provide access to the unexpected spiro derivative 92 containing two pyrazolone units under Knoevenagel conditions, in refluxing ethanol with the presence of a base (pyridine or triethylamine) (Scheme a) . Pyridine base had 45 % yield, whereas triethylamine had 35 %.…”
Section: Organocatalytic Asymmetric Synthesis Of Spiropyrazolones Fusmentioning
confidence: 99%
“…The peak at δ (163.74) ppm is due to C=C-N site linked of 2naphthol with azo group for pyrazolin ring [20], [27]. The signals at δ (47.34) ppm are assigned to the middle and terminal C-C carbon atoms of diaminobutane moiety in the ligand [12], [25], [27]. The mass spectrum data for azo ligand Figure ( 6) showed a molecular ion peak at (m/z =409.6) [25,27].…”
Section: Nmr Spectra For the Azo Ligandmentioning
confidence: 99%
“…The infrared spectral data of azo ligand and its complexes have illustrated in Figures (12)(13)(14)(15) and Table (3). The IR spectra for complexes have compared with those of the free ligand with the intention of determining the coordination sites that can be included in chelation.…”
Section: Ir Spectra Of Azo Ligands and Complexesmentioning
confidence: 99%
See 1 more Smart Citation